Metabolic syndrome in bakery employees: a pilot study - Medina-Quevedo, Pablo (Universidad de Sonora, 2019)
Introduction: The Metabolic Syndrome is an epidemiological indicator of cardiovascular diseases, being present worldwide in 25% of the adult population, doubling the probability of dying and tripling the risk of suffering an acute myocardial infarction or cerebrovascular accidents compared to those that do not have it. Objective: To determine the prevalence of metabolic syndrome in workers of a bakery in Obregon, Sonora. Methodology: An observational, descriptive, transversal pilot study was carried out on a bakery employees. Sampling was non-probabilistic because of availability n=19 employees. We counted on with the corresponding permits and signed informed consent. Data were processed with SPSS version 22. The diagnosis of SMET was determined when three or more of the five ATP III criteria were met. Results: The percentage of metabolic syndrome was 84.2%, with a greater presence in the male gender with 47.4%, all the participants had the presence of at least one ATP III criterion in the study. Conclusions: This study allowed to identify the prevalence of Metabolic Syndrome and at the same time it will be base for new research projects in different contexts.